2020
DOI: 10.1002/adma.202002220
|View full text |Cite
|
Sign up to set email alerts
|

On‐Demand Local Modification of High‐Tc Superconductivity in Few Unit‐Cell Thick Bi2Sr2CaCu2O8+δ

Abstract: High‐temperature superconductors (HTSs) are important for potential applications and for understanding the origin of strong correlations. Bi2Sr2CaCu2O8+δ (BSCCO), a van der Waals material, offers a platform to probe the physics down to a unit‐cell. Guiding the flow of electrons by patterning 2DEGS and oxide heterostructures has brought new functionality and access to new science. Similarly, modifying superconductivity in HTS locally, on a small length scale, is of immense interest for superconducting electroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As shown in our earlier study [14], we selectively deposit Cr on the surface of freshly cleaved few unit cells thick flake of BSCCO, thereby making underneath superconductor insulating, schematically shown in figure 1(b). Following this strategy, we deposit two Cr lines on exfoliated thin BSCCO with a gap in between the Cr lines to define the nanowire, as shown in figure 1(c).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in our earlier study [14], we selectively deposit Cr on the surface of freshly cleaved few unit cells thick flake of BSCCO, thereby making underneath superconductor insulating, schematically shown in figure 1(b). Following this strategy, we deposit two Cr lines on exfoliated thin BSCCO with a gap in between the Cr lines to define the nanowire, as shown in figure 1(c).…”
Section: Methodsmentioning
confidence: 99%
“…These double evaporations aim to avoid deposition of the Cr directly onto the BSCCO, which would result in an insulating behavior of the underlying region, as Cr could capture oxygen atoms from the flakes. [ 33 ] We found that the contact resistance obtained from the deposition of Cr right onto the sample by performing a single evaporation (Au/Cr) was of the order of 1 kΩ, which is ten times higher than the resistance of the contact obtained by the two‐steps evaporation protocol. Figure a,b shows the closeup optical images of two representative devices, one without encapsulation on top of the junction and the other with encapsulation, respectively.…”
Section: Fabricationmentioning
confidence: 98%
“…This two steps evaporation aims at avoiding the deposition of the Cr directly onto the flakes since Cr oxidizes by ripping off oxygen molecules from the BSCCO. This undesired chemical reaction would lead to an insulating behavior of the region underlying the contact layer, strongly degrading the superconducting properties of the entire device [39]. Using this protocol, we obtain the high-quality electrical contact with the areal resistance smaller than 50 kΩµm 2 , an order of magnitude lower than the contact resistance resulting from a single evaporation (Au/Cr) on BSCCO under our conditions.…”
Section: Fabrication Of High-quality Josephson Junctionsmentioning
confidence: 99%